Rapid diagnosis of Talaromyces marneffei infection by metagenomic next-generation sequencing technology in a Chinese cohort of inborn errors of immunity - Liu, Lipin; Sun, Bijun; Ying, Wenjing; Liu, Danru; Wang, Ying; Sun, Jinqiao; Wang, Wenjie; Yang, Mi; Hui, Xiaoying; Zhou, Qinhua; Hou, Jia; Wang, Xiaochuan (Frontiers in Cellular and Infection Microbiology, 2022)
Talaromyces marneffei (T. marneffei) is an opportunistic pathogen. Patients with inborn errors of immunity (IEI) have been increasingly diagnosed with T. marneffei in recent years. The disseminated infection of T. marneffei can be life-threatening without timely and effective antifungal therapy. Rapid and accurate pathogenic microbiological diagnosis is particularly critical for these patients. A total of 505 patients with IEI were admitted to our hospital between January 2019 and June 2022, among whom T. marneffei was detected in 6 patients by metagenomic next-generation sequencing (mNGS), and their clinical and immunological characteristics were summarized. We performed a systematic literature review on T. marneffei infections with published immunodeficiency-related gene mutations. All patients in our cohort were confirmed to have genetic mutations in IL12RB1, IFNGR1, STAT1, STAT3, and CD40LG. T. marneffei was detected in both the blood and lymph nodes of P1 with IL12RB1 mutations, and the clinical manifestations were serious and included recurrent fever, weight loss, severe anemia, splenomegaly and lymphadenopathy, all requiring long-term antifungal therapy. These six patients received antifungal treatment, which relieved symptoms and improved imaging findings. Five patients survived, while one patient died of sepsis after hematopoietic stem cell transplantation. The application of mNGS methods for pathogen detection in IEI patients and comparison with traditional diagnosis methods were investigated. Traditional diagnostic methods and mNGS tests were performed simultaneously in 232 patients with IEI. Compared to the traditional methods, the sensitivity and specificity of mNGS in diagnosing T. marneffei infection were 100% and 98.7%, respectively. The reporting time for T. marneffei detection was approximately 26 hours by mNGS, 3-14 days by culture, and 6-11 days by histopathology. T. marneffei infection was first reported in IEI patients with IL12RB1 gene mutation, which expanded the IEI lineage susceptible to T. marneffei. For IEI patients with T. marneffei infection, we highlight the application of mNGS in pathogenic detection. mNGS is recommended as a front-line diagnostic test for rapidly identifying pathogens in complex and severe infections.